Unlocking the Metalation Applications of TMP-powered Fe and Co(II) bis(amides): Synthesis, Structure and Mechanistic Insights - Logallo, Alessandra; Maddock, Lewis C.H.; Mu, Manting; Gravogl, Lisa; Jin, Na; Peñas-Defrutos, Marconi N.; Meyer, Karsten; García-Melchor, Max; Hevia, Eva (Angewandte Chemie International Edition, 2024)
Typified by LiTMP and TMPMgCl.LiCl, (TMP=2,2,6,6-tetramethylpiperidide), s-block metal amides have found widespread applications in arene deprotonative metalation. On the contrary, transition metal amides lack sufficient basicity to activate these substrates. Breaking new ground in this field, here we present the synthesis and full characterisation of earth-abundant transition metals M(TMP)2 (M=Fe, Co). Uncovering a new reactivity profile towards fluoroarenes, these amide complexes can promote direct M−H exchange processes regioselectively using one or two of their basic amide arms. Remarkably, even when using a perfluorinated substrate, selective C-H metalation occurs leaving C−F bonds intact. Their kinetic basicity can be boosted by LiCl or NBu4Cl additives which enables formation of kinetically activated ate species. Combining spectroscopic and structural studies with DFT calculations, mechanistic insights have been gained on how these low polarity metalation processes take place. M(TMP)2 can also be used to access ferrocene and cobaltocene by direct deprotonation of cyclopentadiene and undergo efficient CO2 insertion of both amide groups under mild reaction conditions.
CRIS-Team Scopus Importer:2024-06-14
Keywords: amide; cobalt; fluoroarenes; iron; metalation